Friction control by multi-shape textured surface under pin-on-disc test. (November 2015) - Zenebe Segu, Dawit; Hwang, Pyung
Abstract: Most of laser surface texturing (LST) research has been conducted on the use of single-shape dimpled effect on the tribological properties. Though under multi-shape LST, the dimpled surface may have a different effect on the tribological properties due to the combined dimples. This paper discussed the effect of multi-shape LST on tribological properties under different conditions. The multi-shape textured surface was fabricated by the laser ablation process by combining different geometric patterns. The tribological tests were conducted by a flat-on-flat tribometer. It was found that the multi-shape LST significantly reduces friction under dry and lubrication conditions, when compared with untextured surfaces. The beneficial effect of textured surface is more pronounced at higher sliding speeds. Highlights: The effect of LST on tribological properties was studied using pin-on-disc test. A new multi-shape LST was made by Nd:YAG laser ablation by combining different geometrical shaps. The textured surfaces improved the tribological properties than the untextured surfaces under dry and lubricated conditions. The beneficial effect of multi-shape LST is more pronounced at higher sliding speeds.